2011
DOI: 10.1002/qua.22893
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical study on photophysical properties of novel bis(BF2)‐2,2′‐bidipyrrins dyes: Effect of variation in monomer structure

Abstract: In this work, monomeric molecules (BODIPY) 4,4-difluoro-1,2,3,5,7-pentamethyl-6-ethyl-4-bora-3a,4a-diaza-s-indacene (1), 4,4-difluoro-1,7-dimethyl-2,3,6-terethyl-8-(4-tolyl)-4-bora-3a,4a-diaza-s-indacene (Ph1), dimeric monomers (bisBODIPY) 2, Ph2, and their packing systems were taken as calculation models to investigate the relationship between monomeric structures and spectral properties of packing systems. Their spectra and carrier transport properties were systemically investigated by density functional the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 55 publications
(17 reference statements)
0
2
0
Order By: Relevance
“…Authors also demonstrated this unexpected elongation of the excited state lifetime to result from complex excited-state dynamics. Upon excitation, the initial excited state resulted in a charge separation state with a reorganization energy of 0.5 eV which is much greater than that reported for similar systems [70]. Following the initial charge separation, a rapid charge recombination occurring in the inverted Markus regime results in the formation of a triplet state lo cated either on the aza-BODIPY or the ferrocene unit.…”
Section: Tablementioning
confidence: 70%
“…Authors also demonstrated this unexpected elongation of the excited state lifetime to result from complex excited-state dynamics. Upon excitation, the initial excited state resulted in a charge separation state with a reorganization energy of 0.5 eV which is much greater than that reported for similar systems [70]. Following the initial charge separation, a rapid charge recombination occurring in the inverted Markus regime results in the formation of a triplet state lo cated either on the aza-BODIPY or the ferrocene unit.…”
Section: Tablementioning
confidence: 70%
“…For example, considering BODIPY-based triads, which are bound to each other using ethynyl-dibutoxyphenyl linkers, it was shown that energy transfer between the terminal BODIPYs occurs primarily by way of through-bond, that is, electron exchange, interactions. 11 Along the same line of thought, BisBODIPY derivatives were investigated using (timedependent) density functional theory (TDDFT), and they were found to have both a high charge-transfer rate and high photoluminiscence efficiency in the solid state, 12 which makes them excellent candidates for ambipolar materials for use in OLEDs for instance.…”
Section: Introductionmentioning
confidence: 99%